Mobile Barcode Based Examination Attendance System - Ullah Khan, Rehman; Chua Yee Wee, Vivian; Wong Sze Lui, Valentina; Inam UlHaq, Much.; Khan, Yahya; Hardyman Barawi, Mohd (International Journal of Engineering and Technology, 2018)
Smartphone usage has revolutionized the world to many settings including that of the education system with numerous potential and realized benefits. While the functions of smartphones, such as text messaging, multimedia, and Internet connectivity, may seem purely recreational, they can be used within the academic institution to manage students attendance to speed up the process of taking attendance by academic instructors, hence reduces time, human errors and redundant works as compared to the manual attendance system. In this paper, we introduced an automatic examination attendance system on smartphones based on the BarcodeÂ to automatically capture student examination attendance. Although many existing systemsÂ (Sudha et al. 2015)Â have been proposed using smartphones for automatic student attendance, there is little study known about a system that is specifically designed for capturing student examination attendance. The main difference among our system and existing systems is that existing systems are using extra hardware device Barcode reader while our system is using smartphone, which highly reduce the cost. Our experiment shows that our proposed student examination attendance system is better for capturing the student attendance information during the examination as compared to the general student attendance systems.Â Â